Класифікація екосистем Житомирського Полісся - Якушенко, Д.М. (Український фітоценологічний збірник, 2005)
Статья посвящена созданию классификации экосистем биогеоценотического уровня Житомирского Полесья. Приведен обзор различных определений понятия «экосистема» и различных подходов к классификации экосистем. Кратко освещены принципы построения классификации. Создана детальная иерархическая классификация экосистем. Разнообразие экосистем составляет 212 единиц VI уровня, 129 — V, 99 — IV, 55 — III, 20 — II уровня и 8 классов экосистем (единиц І уровня). This paper deals with creation of Zhytomyr Polissya biogeocenotic ecosystem's classification. The review of different definitions of the term "ecosystem" and various attempts of ecosystems' classification are made. The principles of classification construction are given brifly. The detailed hierarhical classification of ecosystems is created. The diversity of ecosystems consists of 212 units of VI level, 129 units of V level, 99 units of IV level, 55 — III level, 20 — II level and 8 ecosystem classes (units of І level).